The Department of Atmospheric Science at CSU: a 20 year perspective - Colorado State University. Department of Atmospheric Science, author (Colorado State University. Libraries, 1982)
The CSU Department of Atmospheric Science was founded in 1962. It now has a faculty of 13 (full time), a student body of over 70 graduate students and an additional research associate and supporting staff of about 60. As part of the 20th year reunion celebration of our Department on July 1982 we have taken this occasion to issue this brief report on how our Department has grown and developed through these 20 years. Rather than having one or two people sit-down and write this report by themselves, we have decided to have a number of our current faculty members and Herbert Riehl tell the story of our Department's development in their own unedited words. A wide range of points of view are brought forth, although admittedly from the faculty point-of-view. We recognize that a similar report from our former and present graduate students, staff, and research associates might give a somewhat different perspective. But it is the faculty that have been here the longest and seen our Department evolve the most. The older faculty have primarily concentrated on our Department's development during the 1960's while the younger faculty the developments during the 1970's. This report also lists background statistical information on who has been a member of our faculty, our graduates with their degree thesis titles, and also other information on our Department's current research associates, and support staff.
By department faculty members.
Keywords: Colorado State University. Department of Atmospheric Science; Colorado State University. Department of Atmospheric Science -- Faculty